Complex problem solving and intelligence: empirical relation and causal direction - Wenke, Dorit; Frensch, Peter; Funke, Joachim (Cognition and intelligence, 2005)
INTRODUCTIONThe breadth of human problem solving is truly striking. On the one hand, human problem solving makes possible the most wondrous achievements, such as “an 800-seat airliner with wings that blend smoothly into the fuselage instead of protruding from its sides that is scheduled to be in the air by 2006” (AP news from February 9, 2001). Yet, on the other hand, errors in problem solving can lead to catastrophic and near-catastrophic disasters, such as, for instance, the nuclear reactor accident at Three Mile Island, Pennsylvania, in 1979. Whatever “problem solving” is, and scientists disagree vehemently on the proper meaning of the term, there can be little doubt that it has shaped human culture to an extent that is almost unrivaled by any other human ability.From the inception of the concept of “intelligence,” the ability to solve problems has featured prominently in virtually every definition of human intelligence (e.g., Sternberg & Berg, 1986). In addition, intelligence has often been viewed as one of the best predictors of problem-solving ability (e.g., Putz-Osterloh, 1981; Putz-Osterloh & Lüer, 1981). Thus, whatever the causal relation between the two concepts, prevailing theoretical positions strongly suggest that intelligence and problem solving are related. In this chapter we concentrate on complex rather than on simple problem solving. Our main goal is to review the extent to which the ability to solve complex problems is indeed tied, empirically, to intelligence and to discuss which causal direction holds between the two concepts.
Published online by Cambridge University Press: 23 November 2009
Gesehen am 11.05.2022